Hidden face of chronic obstructive pulmonary disease: effects of patients’ psychiatric symptoms on caregivers’ burden and quality of life - Karagün, Zeynep; Çelik, Deniz; Aydın, Mehmet Sinan; Gündoğmuş, İbrahim; Şipit, Yusuf Tuğrul (The European Research Journal, 2023)
Objectives: Chronic Obstructive Pulmonary Disease (COPD) faces functional and physical limitations and often needs the help of others at certain times in their lives. Patients and caregivers can affect each other psychologically, physically, and socially. This study aims to examine the relationship between the demographic and clinical characteristics of COPD patients and the quality of life and burden of care of caregivers. Methods: The study was carried out with 250 COPD patients who applied to the chest diseases hospital and their caregivers. Hospital Anxiety-Depression Scale (HADS), The Zarit Burden Interview (ZBI), and World Health Organization Quality of Life Scale Short Form (WHOQOL-BREF) scales were applied to the patients. Results: The patients’ gender, age, regular drug use, non-invasive mechanical ventilator use, emergency room admissions, number of hospitalizations, number of intensive care admissions, presence of comorbidities were found to be associated with HADS anxiety and depression scores, ZBI, and WHOQOL-BREF. According to the results of multiple linear regression analysis; it is seen that the patient's gender, NIV use, regular device use, presence of comorbidity, HADS anxiety score, and HADS depression score is an independent predictor of the caregiver's burden (ZBI score); and the patient's NIV use, regular device use, HADS anxiety score and HADS depression score is an independent predictor of the caregiver's WHOQOL-BREF score. Conclusions: It is important to evaluate patients and caregivers in a holistic approach and to realize the factors that may negatively affect them in the early period to take the necessary therapeutic measures.